The influence of playing digital game in distance learning towards students’ speaking skill - Wijanarko, Doni; Hadi, Samsul; Puspitasari, Indah (ELT Forum: Journal of English Language Teaching, 2021)
The lack of class interaction in distance learning makes students can not practice their speaking skill. In another case, the use of digital game have been familiar among students. This situation forces teacher to serve students with creative teaching-learning in the class. Novelty is on the specific game which was used in this research. The researcher experimented to apply digital games namely “Among Us” then investigated the impact on students’ speaking skill. This research aimed to answer the question, how were digital games become an alternative medium to learn English in the distance learning situation? Inherently, this research was a pre-experimental research method with a design of one shoot case study. The main data source in this research was based on students' assessments scores and students’ questionnaire scores then supported by other questionnaires and semi-structured interviews. The averages scores indicate that students were good in speaking skills overall, it could be known by the detailed results of the assessments that were pre-activity 2.64, during-activity 2.50, and post-activity 2.22. Moreover, the results of regression analysis indicated digital games influenced students' achievement and students' motivation. It can be known by the significance of Annova tables results that students’ achievement 0.022 < 0.05 and students motivation 0.000 < 0.05. The Researcher concluded that students were comfortable and more confident to learn and practice their speaking skill during playing the digital game. Finally, through giving correct treatment, digital game activity was possible to be an alternative way to learn English especially to practice speaking skill.